2016
DOI: 10.1111/clr.12954
|View full text |Cite
|
Sign up to set email alerts
|

Excess cement and the risk of peri‐implant disease – a systematic review

Abstract: Excess cement was identified as a possible risk indicator for peri-implant diseases and was more frequently observed with soft tissue healing periods shorter than 4 weeks. To reduce the risk of peri-implant disease associated with excess cement, a crown margin at the level of the mucosal margin providing sufficient access is recommendable, and soft tissue maturation and early follow-ups after restoration placement should be assured.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
169
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(180 citation statements)
references
References 32 publications
6
169
1
4
Order By: Relevance
“…Furthermore, cement‐retained restorations were not found to be at higher risk for peri‐implantitis when compared to screw‐retained reconstructions . Nevertheless, a systematic review emphasized that the rough surface structure of cement remnants may facilitate retention and biofilm formation …”
Section: Observations and Discussionmentioning
confidence: 99%
“…Furthermore, cement‐retained restorations were not found to be at higher risk for peri‐implantitis when compared to screw‐retained reconstructions . Nevertheless, a systematic review emphasized that the rough surface structure of cement remnants may facilitate retention and biofilm formation …”
Section: Observations and Discussionmentioning
confidence: 99%
“…It has been shown that cement remnants are common around implants (Linkevicius, Puisys, Vindasiute, Linkeviciene, & Apse, 2013) and may contribute to the development of peri-implantitis (Sailer, Muhlemann, Zwahlen, Hammerle, & Schneider, 2012;Staubli, Walter, Schmidt, Weiger, & Zitzmann, 2016). It has been shown that cement remnants are common around implants (Linkevicius, Puisys, Vindasiute, Linkeviciene, & Apse, 2013) and may contribute to the development of peri-implantitis (Sailer, Muhlemann, Zwahlen, Hammerle, & Schneider, 2012;Staubli, Walter, Schmidt, Weiger, & Zitzmann, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…23 Small diameter implants were developed for narrow inter-radicular bone sites, regions with a thin alveolar ridge and in replacement of teeth with small cervical diameter. 23 Small diameter implants were developed for narrow inter-radicular bone sites, regions with a thin alveolar ridge and in replacement of teeth with small cervical diameter.…”
Section: Discussionmentioning
confidence: 99%